Public Private Partnership of Waste Management in West Java - Ferza, Ray; Hamudy, Moh Ilham A; Rifki, M Saidi (UI Scholars Hub, 2019)
Despite the prominent reputation of West Java amongst Indonesian local government at the national level, waste management situation has remained not optimal. Fatal waste disasters in the form of landslides have occurred in this province. As a response, the Provincial Government of West Java created several regional policies for waste management. One area affected by policy implementation is the region of Nambo. This policy involved a cooperation scheme between the local government and a private entity public-private partnership (PPP) to establish the Nambo Final Waste Treatment and Processing Facility (known locally as TPPAS). This study seeks to examine and analyze the PPP scheme at TPPAS Nambo and produce a policy recommendation that might answer the study problem. Using descriptive methods and the qualitative approach, this study observes that the cooperation scheme has problems, including its financing scheme and the price determination for the refuse-derived fuel. Our analysis focuses on the situation at Nambo’s waste management, descriptions of the implementation of the PPP policy by the government and the private entity, the financing scheme, and optimization of the cooperation policy. This study covers problems, like imperfect waste management, a mazy financing scheme for waste management, and stalled optimization of the PPP policy for waste management. Finally, we recommend that an effective regulation should be the basis of regional cooperation policy in the area of waste management, and coordination across government agencies is required to ensure improvements in waste management performance in the regions.